PELAKSANAAN KURIKULUM MERDEKA DI MIN 25 PIDIE - Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2024)
This research aimed at obtaining information about the situation of implementing Kurikulum Merdeka in MIN 25 Pidie as well as to identify benefits and barriers which frequently faced. Besides it also aimed to seek the solution to get rid of the problems. The data were collected by the researcher as the main tool of this research and it was involved multy-methods of data collection such as observation, in depth interview and documentation. The result indicated that the implementation of Kurikulum Merdeka in MIN 25 Pidie has been applied gradually and it took process toward better result. It required patience and devotion of all members particularly the teachers and the students. Besides, it is also needed to support the teacher more intensively and thoroughly. Regarding the benefits, the curriculum provided the students more oppurtunity to learn in each stage. It also focus on the essential topics to be studied. However, the obstacles faced by the teacher were to write modules of learning because there are some new terms used which are different from the previous ones. In addition, the teachers were challenged in structuring the LKPD (exercises) for the students. Some solutions had been implemented such as together with the collegues to expand the link as well as to be connected through digital infrmation.